Recent Advances in the Application of the Heck Reaction in the Synthesis of Heterocyclic Compounds: An Update - Heravi, Majid M.; Moradi, Razieh; Malmir, Masoumeh (Current Organic Chemistry, 2018)
Background: The reaction of aryl halides or vinyl halides with activated alkenes in the presence of Palladium-catalyst along with a base for the formation of the C-C bond is called the Heck reaction. This reaction has been employed extensively in the synthesis of heterocyclic compounds. Methodology: We have highlighted these applications in 2010. Conclusion: This review aims to cover the recent application of the Heck reaction in the synthesis of heterocyclic compounds during a period from 2010 to 2017.
Keywords: heterocyclic compounds